2012
DOI: 10.1182/blood-2011-12-381426
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies after multiple myeloma: from 1960s to 2010s

Abstract: Based on small numbers, recent reports from 3 randomized trials have consistently demonstrated more hematologic malignancies in patients treated with lenalidomide as maintenance (vs placebo). This fact has prompted concern and highlighted the association between multiple myeloma and second malignancies. Furthermore, an excess of acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) after multiple myeloma has been known for over 4 decades. Most prior studies have been restricted because of small numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
112
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 64 publications
2
112
0
5
Order By: Relevance
“…SPM included hematologic and solid tumors, and in each trial their risk in the placebo group was 2%-3% versus 7%-8% in the lenalidomide group, with the differences being both statistically and clinically significant. [6][7][8][9] Some reports have also discussed the possibility that thalidomide may potentiate solid SPM, 5,10,11 suggesting an IMiD class effect associated with melphalan exposure.…”
Section: Introductionmentioning
confidence: 99%
“…SPM included hematologic and solid tumors, and in each trial their risk in the placebo group was 2%-3% versus 7%-8% in the lenalidomide group, with the differences being both statistically and clinically significant. [6][7][8][9] Some reports have also discussed the possibility that thalidomide may potentiate solid SPM, 5,10,11 suggesting an IMiD class effect associated with melphalan exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is a risk the factor for both cervical cancer and respiratory tract malignancies, 42 although it is not a risk factor for MM. The increased incidence of hematological malignancies, specifically acute myeloid leukemia/MDS, is well documented in MM patients, 4,6,12,13 where alkylating agents have been considered to be 1 of the main contributing factors, although a role for non-treatment-related factors has also been reported, [4][5][6]8 and the recent discovery of a genotype associated with the development of MDS in MM 22 supports a role for susceptibility genes in this development.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] We have previously shown in a large population-based study that the risk of developing any second malignancy is 26% higher in MM patients compared with the general population; most importantly, they had an 11-fold increased risk of developing acute myeloid leukemia and myelodysplastic syndromes (MDS) and a twofold increased risk of developing nonmelanoma skin cancer. 6 Other studies have found MM patients to have an increased risk of developing certain types of second cancers, such as melanoma, nervous system tumors, and kidney and urinary tract tumors, although mechanisms and risk factors are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median delay between the initiation of therapy and the appearance of a secondary malignancy is of ~45 months in a compilation of 15 trials/studies/series [6]. In this review, the authors also debate on the role of genetic or behavioral factors, inherent to the patient, as well as risk factors associated with the specific characteristics of MM [8].…”
Section: Discussionmentioning
confidence: 99%